Empirical characterization factors to be used in LCA and assessing the effects of hydropower on fish richness - Katrine Turgeon (Elsevier, 2021)
Hydropower is often presented as a clean, reliable, and renewable energy source, but is also recognized for its potential impacts on aquatic ecosystem biodiversity. We used direct empirical data of change in fish species richness following impoundment to develop ecological indicators to be used in Life Cycle Assessment (LCA), and accounting for hydropower impacts on aquatic ecosystems. Data were collected on 89 sampling stations (63 stations located upstream, and 26 located downstream of a dam) distributed in 26 reservoirs from three biomes (boreal, temperate and tropical). Overall, the impact of hydropower on fish species richness was significant in the tropics, of smaller amplitude in temperate biome and minimal in boreal biome, stressing the need for regionalisation when developing indicators. The impact of hydropower was consistent across scales for a given biome (same directionality and statistical significance across sampling stations and reservoirs). However, the indicators were sensitive to the duration of the study (the period over which data have been collected after impoundment), which can underestimate the impacts. This result highlights the need to account for the duration of the transient dynamics to reach a steady state (rate of change in species richness = 0) before developing ecological indicators. By using the LCA approach, our suggested indicators contribute to fill a major gap in assisting decision-makers when evaluating the potential of alternative energy technologies, such as hydropower, to decarbonize the worldwide economy, while minimizing the impacts on aquatic ecosystems.